The Implementation of the STAD Model Assisted by Teaching Aids to Improve Student Learning Outcomes on the Respiratory System in Grade VIII of SMP Kartika IV-6 Ambulu - Zilfin Nabila; H. B. A Jayawardana; Dwi Sucianingtyas Sukamto (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study aimed to improve the learning outcomes of Grade VIII students at SMP Kartika IV-6 Ambulu on the topic of the human respiratory system through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model assisted by teaching aids. The study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart design, conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects were 18 students, and data were collected using a validated multiple-choice test. The results showed an increase in the average score from 73.67 in Cycle I to 83.67 in Cycle II, while classical learning mastery improved from 66.67% to 100%. These findings indicate that the STAD model assisted by teaching aids is effective in improving students’ cognitive learning outcomes and active participation in science learning.